Reverse Pulse Voltammetry at spherical electrodes: Simultaneous determination of diffusion coefficients and formal potentials. Application to Room Temperature Ionic Liquids - Laborda, E; Rogers, E; Martinez-Ortiz, F; Limon-Petersen, J; Rees, N; Molina, A; Compton, R (2009)
A rigorous analytical solution for Reverse Pulse Voltammetry (RPV) at spherical electrodes of all sizes is presented, including the case where the diffusion coefficients of the electroactive species are different. From this solution, the value of RPV for the determination of both diffusion coefficients and the formal potential of the redox couple is demonstrated. The experimental application of the theoretical results is carried out both in ionic liquids and in aqueous solution with mercury microelectrodes of ca. 50 and 10 μm diameters. The former solvent system is of particular interest due to the great importance of these new liquids in which notably unequal diffusion coefficients are commonly found. © 2009 Elsevier B.V. All rights reserved.